Indigenous community-based outreach program: The program and its evaluation - Stearne, Annalee; Wedemeyer, S.; Miller, G.; Miller, S.; McDonald, B.; White, M.; Ramp, J. (Taylor and Francis Ltd, 2009)
In 2004, the Drug and Alcohol Services Association (DASA) in Alice Springs to piloted the Indigenous Community-based Outreach Program. The main aim of this intervention is to provide evidence based follow-up services for clients in a post-treatment situation. In particular, this Program is to provide community outreach for Indigenous people who need specialised support to reduce the harm associated with substance use. DASA opened a combined detoxification and rehabilitation facility two years ago in Alice Springs. The Indigenous Outreach Team were paramount for the success of the facility; the Team refer many clients, and continue to provide support to clients throughout the rehabilitation process and eventually back into their normal lives, a process that can take well over a year.From its inception, the National Drug Research Institute progressively evaluated the Program. Using measures of success identified at the establishment of the Program, the results of the evaluation will be discussed, showing the evolution into the Program that is operating two years later.As this Program was funded as a pilot, evaluation has been integral to program sustainability. With evidence from the evaluation, the Program attracted recurrent funding and has expanded to employ three additional outreach workers. The Indigenous Community-based Outreach Program was awarded the 2008 National Drug and Alcohol Award for Excellence in Treatment and Support. This paper highlights the value and benefit of well-planned progressive evaluation for community-based interventions, as well as the importance of a Program evolving to meet the needs of the organisation and clientele.